JURIDICAL ANALYSIS ON THE VALIDITY OF PROPERTY SALE ERTIFICATE BY PPAT (OFFICIAL EMPOWERED TO DRAW UP LAND DEEDS) FOR FOREIGNERS IN INDONESIA - NINDYA CAESY AIDITA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Suprayitno, SH, MKn PPAT is liable for the deeds he has drawn up so that when there s a dispute, a civil sanction will be imposed upon him. A PPAT’s deed is evidence with a complete legal force, but when later on they are considered as underhanded deeds or they are null and void according to a Court’s Verdict which is final and conclusive (inkracht) so that it is considered illegal and harms other parties, the PPAT is liable and is required to pay compensation. The regulation on making property sale certificate for foreigners in Indonesia is that by making a request for right of use for foreigners, the original certificate is changed to right of use, and transaction can be done. Foreigners can buy or build their own houses on the right of use land of the State land or the right of use on ownership land, or buy units of apartment built on a right of use land or on the State land. Legal protection for foreigners who make property sale certificate is found in Article 4 of UUPA which states that foreigners who live in Indonesia are allowed to have the right of use so that as buyers, they can have legal protection, but when they want to buy ownership land, it has to be changed to the right of use.Keywords: Validity of Property Sale Certificate, PPAT, Foreigners